2009
DOI: 10.1182/blood-2008-11-191577
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DKK1 mAb (BHQ880) as a potential therapeutic agent for multiple myeloma

Abstract: Decreased activity of osteoblasts (OBs) contributes to osteolytic lesions in multiple myeloma (MM). IntroductionA cardinal clinical feature of multiple myeloma (MM) is the presence of osteolytic bone lesions. Myeloma cells disrupt the delicate balance between bone formation and bone resorption. 1,2 Various clinical observations 3 and experimental studies 4,5 have linked the level of MM bone disease with disease burden. Increased osteoclastic activity and its molecular basis have long been considered a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
297
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 370 publications
(308 citation statements)
references
References 49 publications
10
297
0
1
Order By: Relevance
“…Since TNF-a seemed to increase the levels of other canonical Wnt proteins, we investigated the activation of the canonical Wnt signaling pathway with anti-Dkk1 antibodies. Stimulatory effects of anti-Dkk1 antibodies have recently been reported in mouse primary osteoblasts [17], and are consistent with the beneficial effects of anti-Dkk1 antibodies on bone formation in vivo [10,17,35,36]. In our experiments, blocking Dkk1 slightly increased TNAP expression in osteoblasts differentiating from human MSCs.…”
Section: Discussionsupporting
confidence: 91%
“…Since TNF-a seemed to increase the levels of other canonical Wnt proteins, we investigated the activation of the canonical Wnt signaling pathway with anti-Dkk1 antibodies. Stimulatory effects of anti-Dkk1 antibodies have recently been reported in mouse primary osteoblasts [17], and are consistent with the beneficial effects of anti-Dkk1 antibodies on bone formation in vivo [10,17,35,36]. In our experiments, blocking Dkk1 slightly increased TNAP expression in osteoblasts differentiating from human MSCs.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo studies using both murine and humanized models of MM-bone disease confirmed the bone-anabolic properties of DKK1 antagonists, with increased bone formation, increased OB number and improvement of osteolytic lesions [31,33,34]. Importantly, two studies showed a significant reduction in tumor burden, mainly as an indirect effect via modification of the tumor microenvironment by DKK1 inhibition [31,33]. A clinical trial (NCT00741377) has been opened in 2008 to assess safety and tolerability as well as efficacy of the DKK1 inhibitor BHQ880 in combination with standard chemotherapy with or without bisphosphonates in relapsed or refractory MM patients.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 82%
“…BHQ880 and DKK1 Antagonists BHQ880 is a clinical grade neutralizing antibody against DKK1 (Novartis), which promotes OB differentiation by reversing the negative effects of MM cells on OB formation and inhibits IL-6 production by BMSC, thereby blocking tumor cells proliferation [33]. In vivo studies using both murine and humanized models of MM-bone disease confirmed the bone-anabolic properties of DKK1 antagonists, with increased bone formation, increased OB number and improvement of osteolytic lesions [31,33,34].…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 95%
See 2 more Smart Citations